Artificial Intelligence and Nursing Informatics in Orthopaedic Rehabilitation: A Systematic Review of Predictive and Monitoring Applications - Tomy Suganda; Eli Amaliyah; Agung Pamuji Nugroho (NERS Jurnal Keperawatan, 2026)
Orthopaedic rehabilitation demands continuous assessment and personalized care. The integration of Artificial Intelligence (AI) into Nursing Informatics (NI) offers opportunities to enhance prediction, monitoring, and decision-making in patient recovery. This review synthesizes recent evidence on AI applications within NI for orthopaedic rehabilitation, focusing on predictive, monitoring, integrative, and ethical dimensions. Following PRISMA 2020, searches were conducted in Scopus and ScienceDirect (2016–2025) for English full-text research and review articles. Data extraction and quality appraisal used the JBI Critical Appraisal Checklist, and findings were analysed thematically. Ten studies met inclusion criteria. AI predictive models improved risk anticipation and recovery forecasting, while monitoring systems enhanced real-time functional assessment. Integration with NI facilitated data interoperability and decision support through Electronic Health Records (EHRs). However, challenges remain limited digital literacy, privacy risks, and ethical concerns about algorithmic transparency. Integrating AI into nursing informatics enhances data-driven, patient-centered rehabilitation. Success depends on digital competency, ethical governance, and interprofessional collaboration to ensure AI supports, rather than replaces, human judgment in intelligent nursing practice.